Optimalisasi Ekosistem: Strategi Cerdas UEA Mendulang Keuntungan dari Hedge Fund Besar tanpa Mengorbankan Prinsip Syariah - Habib Fitrah; Maryam Batubara (CV. ALIM'SPUBLISHING, 2026)
This study examines how the United Arab Emirates (UAE) capitalizes on global hedge funds while addressing Sharia concerns related to short-selling, gharar, and riba. Using a qualitative literature review of academic studies, regulatory documents, and industry reports, the study identifies five non-oil economic mechanisms underlying the UAE’s strategy: revenue generation through real economic activities such as leasing, licensing, and consumption; Emiratization to facilitate knowledge transfer and local workforce absorption; global asset control through sovereign wealth funds; economic stability as a safe haven during crises; and technology transfer enabled by innovative regulations in digital assets and financial artificial intelligence. Rather than establishing Sharia-compliant hedge funds, which have historically experienced limited success, the UAE prioritizes ecosystem optimization through Sharia authorities, Islamic structured products based on wa’ad and murabahah, fintech integration, and a liquid sukuk market. The strategy aligns with maqashid al-Sharia through risk-sharing mechanisms, social responsibility, and fintech-based risk management. The study contributes a five-mechanism framework to Islamic finance literature and provides a potential model for Muslim countries seeking global investment without relying on dedicated Sharia-compliant hedge funds.